2018
DOI: 10.1101/451047
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of tumor stromal architecture on therapy response and clinical progression

Abstract: Advances in molecular oncology research culminated in the development of targeted therapies that act on defined molecular targets either on tumor cells directly (such as inhibitors of oncogenic kinases), or indirectly by targeting the tumor microenvironment (such as anti-angiogenesis drugs). These therapies can induce strong clinical responses, when properly matched to patients. Unfortunately, most targeted therapies ultimately fail as tumors evolve resistance. Tumors consist not only of neoplastic cells, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Fibroblasts can influence the vast majority of the mechanisms mentioned above by either (1) supporting specific subpopulations of cancer cells, such as stem-like cancer cells [ 59 , 60 , 61 , 62 , 63 ], (2) rewiring the signalling networks in cancer cells [ 64 , 65 , 66 , 67 ] and (3) modulating the tumour microenvironment, namely immune cells [ 68 ]. Interestingly, spatial analysis has revealed that the close proximity of malignant cells to stromal fibroblasts is associated with an increased cycling capacity of cancer cells after therapy, hinting to a protective role of fibroblasts [ 69 ].…”
Section: Fibroblastsmentioning
confidence: 99%
“…Fibroblasts can influence the vast majority of the mechanisms mentioned above by either (1) supporting specific subpopulations of cancer cells, such as stem-like cancer cells [ 59 , 60 , 61 , 62 , 63 ], (2) rewiring the signalling networks in cancer cells [ 64 , 65 , 66 , 67 ] and (3) modulating the tumour microenvironment, namely immune cells [ 68 ]. Interestingly, spatial analysis has revealed that the close proximity of malignant cells to stromal fibroblasts is associated with an increased cycling capacity of cancer cells after therapy, hinting to a protective role of fibroblasts [ 69 ].…”
Section: Fibroblastsmentioning
confidence: 99%
“…Fibroblasts can be of influence by either (i) sustaining specific subtypes of neoplastic cells, such as CSCs [ 267 ], (ii) rewiring the signalling networks in cancer cells [ 80 ], or (iii) modulating immune cells [ 268 ]. All this leads us to the conclusion that both the presence and the amount of CAFs will be determinants in the final outcome in terms of tumour progression, dissemination, and chemoresistance [ 269 ].…”
Section: Tumour Stroma and Therapeutic Resistancementioning
confidence: 99%
“…Cancer-associated fibroblasts (CAF) are known to promote cancer cell growth and drug resistance [29][30][31][32][33]. In particular, recent studies revealed the impact of fibroblast location on the outcomes of continuous therapy [30,34,47]. The distribution of CAFs in real tumor tissues is diverse, which is difficult to categorize [32,[35][36][37].…”
Section: Cancer Associated Fibroblast-mediated Drug Resistancementioning
confidence: 99%